Plant and animal homeodomains use convergent mechanisms for intercellular transfer - Tassetto, Michel; Maizel, Alexis (EMBO reports, 2005)
Homeoproteins are defined by the structure of their DNA‐binding domain, the homeodomain. Intercellular transfer of homeoprotein was observed ex vivo between animal cells and in vivo in higher plants. In the latter case, transfer is through intercytoplasmic channels that connect plant cells, but these do not exist in animals. Here, we show that the homeodomain of KNOTTED1, a maize homeoprotein, is transferred between animal cells and that a mutation in the homeodomain blocking the intercellular transfer of KNOTTED1 in plants also inhibits the transfer of the KNOTTED1 homeodomain in animal cells. This mutation decreases nuclear addressing, and its effect on nuclear import and intercellular transfer is reverted by the addition of an ectopic nuclear localization signal. We propose that, despite evolutionary distance and the differences in multicellular organization, similar mechanisms are at work for intercellular transfer of homeoprotein in plants and animals. Furthermore, our results suggest that, at least in animals, homeodomain secretion requires passage through the nucleus.